The practice of cultural ecology: network connectivity in the creative economy. Issue 2 (2nd April 2016) - Dovey, Jonathan; Moreton, Simon; Sparke, Sarah; Sharpe, Bill
ABSTRACT: This paper reflects on approaches to collaborative knowledge exchange projects between UK universities and the creative economy. It develops a preliminary account of cultural ecology as a systematic approach to producing impact in the creative economy. It argues that such an approach is a powerful way to aggregate micro-businesses and small and medium sized enterprises in a meaningful network of new relationships. The paper uses social network analysis software to begin to visualise the pattern of relationships that constitute the ecosystem. The paper reports on the work of the Research and Enterprise for Arts and Creative Technologies Hub, one of four Knowledge Exchange Hubs for the Creative Economy established by the Arts and Humanities Research Council.